Getting Money By Game Just From Smartphone In Digital Era - Rahman Hidayat (Hikamatzu | Journal of Multidisciplinary, 2024)
In the digital era, the landscape of income generation has undergone a transformative shift, with individuals now capitalizing on the lucrative prospect of earning money through smartphone-based gaming. The convergence of technology and entertainment has given rise to a novel avenue where users can harness their gaming prowess to unlock financial opportunities. Through various gaming platforms and applications, individuals navigate a virtual realm, strategically competing or collaborating to accrue in-game currencies, rewards, and ultimately, real-world monetary gains. This phenomenon reflects the evolving dynamics of work and leisure in the digital age, where the boundaries between recreation and income generation blur, offering a glimpse into the innovative ways individuals leverage their skills and time within the palm of their hands to secure financial returns..